The Weimar Triangle: France, Germany, Poland in the Middle East. United Arab Emirates Perspective - Krzymowski, Adam (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2021)
The article’s scientific goal is to investigate the Weimar Triangle countries’ relations with the United Arab Emirates. Therefore, the author asks the research question. Are the Weimar Triangle states’ role and significance increasing in the external dimension of the European Union? Based on the example of the United Arab Emirates, the research adopted a hypothesis. It is the statement that after Brexit, the Weimar Triangle countries have a chance to improve their importance in the EU external activities. Apart from case studies, to revise the hypothesis, the author performed a meticulous comparative analysis. Moreover, the research implemented International Practice Theory as an appropriate tool to investigate the presented issue. This empirical research and its findings resulted from over ten years of the author’s direct observation, analysis, and participation in many initiatives, both in the European Union and in the United Arab Emirates. The Middle East for the Weimar Triangle countries is more significant than just from a trade potential perspective. The situation in this region is also affecting Europe, as well as global security architecture. For this reason, one should develop a coherent and comprehensive EU foreign and security policy towards the region, and the Weimar Triangle formula should be one of its pillars.

Celem naukowym artykułu jest zbadanie stosunków państw Trójkąta Weimarskiego ze Zjednoczonymi Emiratami Arabskimi. Dlatego też, autor stawia pytanie badawcze. Czy rola i znaczenie państw Trójkąta Weimarskiego wzrasta w zewnętrznym wymiarze Unii Europejskiej? Na przykładzie Zjednoczonych Emiratów Arabskich w badaniu przyjęto hipotezę. Jest to stwierdzenie, że po Brexicie, państwa Trójkąta Weimarskiego mają szansę zwiększyć swoje znaczenie w działaniach zewnętrznych UE. Oprócz studiów przypadków, w celu zrewidowania hipotezy, autor przeprowadził skrupulatną analizę porównawczą. Ponadto, jako odpowiednie narzędzie do zbadania przedstawionego zagadnienia, przyjęto Teorię Praktyki Międzynarodowej (International Practice Theory). Niniejsze badania empiryczne i jego wyniki są rezultatem ponad dziesięciu lat autora bezpośredniej obserwacji, analiz i uczestniczenia w wielu inicjatywach, zarówno Unii Europejskiej, jak i Zjednoczonych Emiratów Arabskich. Bliski Wschód dla krajów Trójkąta Weimarskiego jest ważniejszy niż tylko z perspektywy potencjału handlowego. Sytuacja w tym regionie ma również wpływ na Europę i globalną architekturę bezpieczeństwa. Dlatego też, należy rozwijać spójną i kompleksową politykę zagraniczną i bezpieczeństwa UE, wobec tego regionu, a jednym z jej filarów powinna być formuła Trójkąta Weimarskiego.
Trójkąt Weimarski: Francja, Niemcy, Polska na Bliskim Wschodzie. Perspektywa Zjednoczonych Emiratów Arabskich
Keywords: Weimar Triangle; Middle East; France; Germany; Poland; United Arab Emirates; European Union; Trójkąt Weimarski; Bliski Wschód; Francja; Niemcy; Polska; Zjednoczone Emiraty Arabskie; Unia Europsejska